Estructura poblacional y consanguinidad en Dota, Costa, Rica, 1888-1962 - Barrantes, Ramiro (Revista de Biología Tropical, 1978)
A study of consanguinity and population structure was carried out in a sample of 498 consanguineous (MC) and 570 non-consanguineous matings (MNC) in the Parrish of Dota, Costa Rica, during a period of 75 years. The inbreeding coefficient (F) shows fluctuations in time (476 to 194 x 10-5) with an increase from 1888 to 1917, followed by a decrease in the last years but remains high in nonmigrant marriages. There is a high frequency of unions among second cousins. The endogamy percentage is high, greater in MC (80%) than in MNC (61%). Exogamy tends to diminish with time among both types of union. Effects of age distributions in the groups were not found. Marital and migrational distances are short and tend to become shorter in the final periods. There is a positive correlation (r = 0,71 ; p <0,05) between these distances in MC but not in MNC; distances are shorter in MC. Inmigration is minimal and reduced to short distances. Post-marital movement is intense (37% and involves greater distances. Emigratory behavior is identical in MC and MNC.